The impact of legalizing unauthorized immigrants - Cynthia Bansak; Sarah Pearlman (IZA World of Labor, 2021)
Countries have adopted a variety of legalization programs to address unauthorized immigration. Research in the US finds improved labor market outcomes for newly authorized immigrants. Findings are more mixed for European and Latin American countries where informal labor markets play a large role and programs are often small scale. Despite unclear labor market outcomes and mixed public support, legalization will likely continue to be widely used. Comprehensive legislation can address the complex nature of legalization on immigrants and on native-born residents.
Keywords: F22; J15; J61; 330; legalization; regularization; immigration